Examining between Exchange Rate Volatility and Natural Rubber Prices: Engle-Granger Causality Test - Khin, Aye Aye; Chau, Wong Hong; Yean, Ung Leng; Keong, Ooi Chee; Leh Bin, Raymond Ling (International Journal of Economics and Financial Issues, 2017)
There are two objectives of this study, first, it is to determine the impact of exchange rate volatility on Malaysian natural rubber (NR) prices of (SMR20 and RSS4); second, it is to forecast a short-term exchange rate (ERP) of Malaysian Ringgit (RM per USD) and NR prices strongly represented in the Malaysian NR market. The granger causality test is first analyzed using the vector error correction model (VECM) with the more efficient Engle-Granger causality procedure. Both short-term ERP and NR prices ex-ante forecasts are tested using Pindyck and Rubinfeld’s procedures. The result shows the RSS4 NR price Granger-causes the SMR20 NR price and also ERP with unidirectional causality relationship. Both ERP and NR prices forecasts would be on a slightly increasing trend from January to June 2016. It was due to government and traders changing their behaviour by increasing domestic consumptions for the stabilization of the NR supply-demand balance. Keywords: Exchange Rate Volatility, Forecasting, Malaysian Natural Rubber Price JEL Classifications: C1, C2, D4, F31, F37